The Impact of Supply Chain Management on Competitive Advantage of Handicraft SMEs in Bandar Lampung - Pipiet Mutiara (BRIDGE : The Multidisciplinary Research Portal, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic growth, particularly in the era of the ASEAN Economic Community (AEC), which demands higher global competitiveness. This study evaluates the impact of Supply Chain Management (SCM) practices on competitive advantage and organizational performance among handicraft MSMEs in Bandar Lampung City. Data were obtained from 55 MSME members registered with the Bandar Lampung Cooperative and MSME Office through a closed-ended questionnaire using a Likert scale of 1-5. The data were then analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 3. The results indicate a significant positive impact of SCM practices on organizational performance, SCM practices on competitive advantage, and competitive advantage on organizational performance. Thus, effective supply chain management practices can enhance the competitive advantage and organizational performance of MSMEs, strengthening their position in global competition.